Global Objects : Toward a Connected Art History - Cooke, Edward S. (Book collections on Project MUSE., 2022)
"The established narrative of art history is traditionally narrated through national or cultural lenses that focus on specific artistic practices characteristic of a given nation or culture: bronze in ancient China, architecture in ancient Rome, or oil painting in early modern Europe, for instance. These practices accord with a modern Western frame of reference, which defines art as the fine arts and relegates other works to the category of craft. Objects of use are rarely included-dismissed as insignificant, merely functional, lacking in imagination, or even primitive. The result has been a fragmented, hierarchical field in which broad comparative strokes have proved difficult to sustain, and longstanding biases have become standardized. This book challenges the hierarchy of genres and materials, as well as the concept of singular artistic centers with linear chronological narratives. Author Ned Cooke is one of the leading scholars working on the history of material culture within art history. Taking a thematic approach to interconnected histories and questioning the accepted notion of art as a category that privileges certain modes of production, Cooke focuses on quotidian materials-including fiber, clay, wood, and metal-and the so-called decorative arts as embodiments of a more inclusive human history of visual culture. Through an exploration of the conception, production, circulation, and ongoing social life of objects over a broad period of time and geography, he develops a more global and complex view of culture in which initiative, emulation, adaptation, and innovation flow in multiple directions, and objects operate locally, regionally, and globally, often at the same time. Eschewing traditional binaries of east versus west and fine art versus decorative art, this book offers a radical, non-normative guide to thinking about a connected world art history"--